Cardiovascular Risk Factors in Adult Patients with Type II Diabetes in Western Kenya - Barasa M Ambrose; Cherop Doreen; G. R. Neel; Kowanga Kenedy; Aziz Katabasi; Cedrick IZERE; Jackim. N (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study investigates the risk factors associated with cardiovascular disorders among adult patients with type II diabetes in western Kenya. Acrossectional quantitative study was conducted among randomly selected type II diabetic patients aged 18 years and above. Data was collected through questionnaires and medical examination. The study found a high prevalence of obesity, hypertension and dyslipidemia among the participants indicating a significant risk of cardiovascular disorders in this population.